Analisis Penyerapan Tenaga Kerja pada Industri Mikro Kecil (IMK) di Kabupaten Padang Pariaman - Elwita Syafrilia; Joan Marta; Dwirani Puspa Artha (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of business capital, total productionvalue, type of place of business, type of indstry and utilization of internettechnology on the labor absorption of micro and small industries in PadangPariaman District. This type of research is descriptive and associative research,the data used is secondary data (cross section) in 2021 obtained from relatedinstitutions. The analytical method used is Poisson regression analysis modelassisted by STATA 16 software. The result show that; (1) business capital has asignificant and positive effect on the labor absorption of micro and smallindustries in Padang Pariaman District; (2) total production value has asignificant and positive effect on the labor absorption of micro and smallindustries in Padang Pariaman District; (3) type of place of business has asignificant and positive effect on the labor absorption of micro and smallindustries in Padang Pariaman District; (4) the type of non metallic mineralsindustry, food industry and other industries have a significant effect on thelabor absorption of micro and small industries in Padang Pariaman District,while the wood industry does not have a significant effect on the laborabsorption of micro and small industries in Padang Pariaman District; (5)utilization of internet technology has a significant and positive effect on thelabor absorption of micro and small industries in Padang Pariaman District.